Wellbeing, alcohol use and sexual activity in young teenagers: findings from a cross-sectional survey in school children in North West England - Kelly Imogen E; Downing Jennifer; Jones Hayley; Briant Linford B; Bellis Mark A; Phillips-Howard Penelope A; Bird Timothy; Cook Penny A (BMC, 2010)
Abstract Background Adolescent health is a growing concern. High rates of binge drinking and teenage pregnancies, documented in the UK, are two measures defining poor wellbeing. Improving wellbeing through schools is a priority but information on the impact of wellbeing on alcohol use, and on sexual activity among schoolchildren is limited. Methods A cross-sectional survey using self-completed questionnaires was conducted among 3,641 schoolchildren aged 11-14 years due to participate in a sex and relationships education pilot programme in 15 high schools in North West England. Bivariate and multivariate analyses were conducted to examine the relationship between wellbeing and alcohol use, and wellbeing and sexual activity. Results A third of 11 year olds, rising to two-thirds of 14 year olds, had drunk alcohol. Children with positive school wellbeing had lower odds of ever drinking alcohol, drinking often, engaging in any sexual activity, and of having sex. General wellbeing had a smaller effect. The strength of the association between alcohol use and the prevalence of sexual activity in 13-14 year olds, increased incrementally with the higher frequency of alcohol use. Children drinking once a week or more had 12-fold higher odds of any sexual activity, and 10-fold higher odds of having sex. Rare and occasional drinkers had a significantly higher odds compared with non-drinkers. Conclusions The relationship between wellbeing and alcohol use, and wellbeing and sexual activity reinforces the importance of initiatives that enhance positive wellbeing in schoolchildren. The association between alcohol use and sexual activity highlights the need for integrated public health programmes. Policies restricting alcohol use may help reduce sexual exposure among young teenagers.